Solid electrolyte capacitor and method for manufacturing the same

By adopting a double-layer solid electrolyte layer structure in tantalum capacitors, combined with electrolytic polymerization and chemical polymerization technology, the shortcomings of existing tantalum capacitors in terms of heat resistance and moisture resistance are solved, and capacitors with high capacity, high voltage and high reliability are achieved.

CN112825287BActive Publication Date: 2025-03-14SAMSUNG ELECTRO MECHANICS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202010710322.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-11-20
Filing Date
2020-07-22
Publication Date
2025-03-14
Estimated Expiration
2040-07-22

AI Technical Summary

Technical Problem

Existing tantalum capacitors have shortcomings in terms of heat resistance and moisture resistance, which are difficult to meet the needs of high reliability and high capacity.

Method used

A bilayer solid electrolyte layer structure is adopted, wherein the first layer is formed by electrolytic polymerization of conductive polymers, the second layer is formed by chemical polymerization of conductive polymers, and a dielectric oxide layer is formed on the sintered body as an insulating layer.

Benefits of technology

It realizes high-capacity, high-voltage solid electrolyte capacitors with excellent heat resistance and moisture resistance, which can meet the needs of small and high-capacity products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112825287B_ABST
    Figure CN112825287B_ABST
Patent Text Reader

Abstract

The present disclosure provides a solid electrolyte capacitor and a method for manufacturing the same, the solid electrolyte capacitor comprising: a sintered body formed by sintering a molded body containing metal powder; and a solid electrolyte layer disposed on the sintered body, wherein the solid electrolyte layer comprises a first layer containing an electrolytically polymerized conductive polymer disposed on the sintered body and a second layer containing a chemically polymerized conductive polymer disposed on the first layer.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application claims the benefit of priority from Korean Patent Application No. 10-2019-0149385 filed on November 20, 2019, in the Korean Intellectual Property Office, the disclosure of which is incorporated herein by reference. Technical Field

[0002] The present disclosure relates to a solid electrolytic capacitor and a method for manufacturing the same, and to a solid electrolytic capacitor excellent in heat resistance and moisture load resistance and a method for manufacturing the same. Background Art

[0003] Tantalum (Ta) material is a metal widely used in various industries such as electrical, electronic, mechanical, chemical, aerospace, and military fields due to its mechanical and physical properties such as high melting point, excellent ductility, and excellent corrosion resistance.

[0004] In particular, since tantalum materials can form the most stable anodic oxide film, tantalum has been widely used as a material for forming an anode for a small capacitor.

[0005] In addition, due to the rapid development of IT industries such as electronics, information and communications, the use of tantalum materials is growing rapidly at a rate of 10% per year.

[0006] Tantalum capacitors have the following structure: tantalum oxide (Ta2O5) is formed on the surface of tantalum as an electrode metal by an anodizing method using gaps that occur when tantalum powder is sintered and hardened, and tantalum oxide (Ta2O5) is used as a dielectric to form a manganese dioxide (MnO2) layer or a conductive polymer layer thereon as a solid electrolyte.

[0007] In addition, due to derivation of the cathode electrode, a carbon layer is formed on the manganese dioxide (MnO 2 ) layer or the conductive polymer layer and a silver (Ag) layer is formed on the carbon layer as a metal layer.

[0008] With the recent development of small and high-capacity products, capacitors are also required to have high capacitance, low equivalent series resistance (ESR), low equivalent series inductance (ESL), and excellent direct current bias (DC bias) characteristics.

[0009] Generally, in a tantalum capacitor, a solid electrolyte layer is formed by applying an electrolytic polymerization technique or a chemical polymerization technique.

[0010] However, each of the electrolytic polymerization technique and the chemical polymerization technique has technical limitations and disadvantages.

[0011] Therefore, there is an increasing demand for the development of high-reliability tantalum capacitors that are excellent in heat resistance and moisture load resistance among high-reliability capacitors (particularly, capacitors for electric fields). Summary of the invention

[0012] An aspect of the present disclosure is to provide a solid electrolytic capacitor and a method for manufacturing the same, and relates to a solid electrolytic capacitor excellent in heat resistance and moisture load resistance and a method for manufacturing the same.

[0013] A solid electrolyte capacitor comprises: a sintered body formed by sintering a molded body containing metal powder; and a solid electrolyte layer disposed on the sintered body, wherein the solid electrolyte layer comprises a first layer containing an electrolytically polymerized conductive polymer disposed on the sintered body and a second layer containing a chemically polymerized conductive polymer disposed on the first layer.

[0014] According to another aspect of the present disclosure, a method for manufacturing a solid electrolyte capacitor includes the following operations: forming a sintered body by sintering; forming a first layer containing an electrolytically polymerized conductive polymer on the sintered body by electrolytic polymerization; and forming a second layer containing a chemically polymerized conductive polymer on the first layer by chemical polymerization. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] The above and other aspects, features and other advantages of the present disclosure will be more clearly understood through the following detailed description taken in conjunction with the accompanying drawings, in which:

[0016] Figure 1 is a cross-sectional view of a solid electrolytic capacitor according to an embodiment of the present disclosure;

[0017] Figure 2 yes Figure 1 an enlarged view of region A in FIG. 1 ; and

[0018] Figure 3 is a manufacturing process diagram of a solid electrolytic capacitor according to another embodiment of the present disclosure. DETAILED DESCRIPTION

[0019] The present disclosure may be illustrated in many different forms and should not be construed as being limited to the specific embodiments set forth herein. Rather, these embodiments are provided so that the present disclosure will be thorough and complete, and will fully convey the scope of the present disclosure to those skilled in the art. Therefore, for clarity of description, the shapes and sizes of the elements in the accompanying drawings may be exaggerated, and in the accompanying drawings, the elements indicated by the same reference numerals are the same elements.

[0020] The values ​​of parameters used to describe such as 1-D dimensions of elements (including but not limited to "length", "width", "thickness", "diameter", "distance", "gap" and / or "size"), 2-D dimensions of elements (including but not limited to "area" and / or "size"), 3-D dimensions of elements (including but not limited to "volume" and / or "size"), and properties of elements (including but not limited to "roughness", "density", "weight", "weight ratio" and / or "molar ratio") can be obtained by the methods and / or tools described in the present disclosure. However, the present disclosure is not limited thereto. Other methods and / or tools understood by those of ordinary skill in the art may also be used even if not described in the present disclosure.

[0021] Hereinafter, embodiments of the present disclosure will be described as follows with reference to the accompanying drawings.

[0022] Figure 1 is a cross-sectional view of a solid electrolytic capacitor according to an embodiment of the present disclosure.

[0023] Figure 2 yes Figure 1 Magnified view of area A in FIG.

[0024] Reference Figure 1 and Figure 2 , a solid electrolyte capacitor according to an embodiment of the present disclosure includes: a sintered body 110 formed by sintering a molded body including metal powder; and a solid electrolyte layer 130 disposed on the sintered body 110. The solid electrolyte layer 130 includes a first layer 130a including an electrolytically polymerized conductive polymer disposed on the sintered body 110 and a second layer 130b including a chemically polymerized conductive polymer disposed on the first layer 130a.

[0025] The solid electrolytic capacitor may further include an anode lead 120 having an insertion region located inside the sintered body 110 and a non-insertion region located outside the sintered body 110 .

[0026] The sintered body 110 may be formed by sintering a molded body including metal powder and a binder.

[0027] Specifically, metal powder, a binder, and a solvent may be mixed and stirred at a predetermined ratio, and the mixed powder may be pressed into a cuboid form and then sintered at a high temperature and high vibration.

[0028] The metal powder is not particularly limited as long as it can be used for the sintered body of the solid electrolytic capacitor according to the embodiment of the present disclosure, and the metal powder may be one or more selected from the group consisting of, for example, tantalum (Ta), aluminum (Al), niobium (Nb), vanadium (V), titanium (Ti) and zirconium (Zr).

[0029] In particular, the sintered body of the solid electrolytic capacitor according to the embodiment of the present disclosure may be formed using tantalum (Ta) powder.

[0030] The binder is not particularly limited, and may be, for example, a cellulose-based binder.

[0031] The cellulose-based binder may be one or more selected from the group consisting of nitrocellulose, methylcellulose, ethylcellulose, and hydroxypropylcellulose.

[0032] In addition, before the mixed powder is pressed, the anode lead 120 may be inserted into the mixed powder and mounted on the mixed powder so as to be offset from the center.

[0033] According to an embodiment of the present disclosure, a dielectric oxide layer may be formed on the sintered body 110 as an insulating layer.

[0034] That is, the dielectric oxide layer may be formed by growing an oxide film (eg, Ta 2 O 5 ) on the surface of the sintered body 110 through a chemical treatment process using an electrochemical reaction.

[0035] In this case, the dielectric oxide layer turns the sintered body 110 into a dielectric.

[0036] A solid electrolyte layer 130 having a cathode polarity may be applied on the dielectric oxide layer.

[0037] The solid electrolyte layer 130 is not particularly limited, and may be formed using, for example, one or more selected from the group consisting of manganese dioxide (MnO 2 ) and a conductive polymer, and in particular, may be formed using a conductive polymer.

[0038] Specifically, in the case of using a conductive polymer for the solid electrolyte layer, a cathode layer having a conductive polymer cathode may be formed on the outer surface of the sintered body 110 including the insulating layer by chemical polymerization of 3,4-ethylenedioxythiophene (EDOT) or electrolytic polymerization of pyrrole monomers.

[0039] With the recent development of small and high-capacity products, capacitors are also required to have high capacitance, low equivalent series resistance (ESR), low equivalent series inductance (ESL), and excellent DC bias characteristics.

[0040] Generally, in a tantalum capacitor, a solid electrolyte layer is formed by applying an electrolytic polymerization technique using a pyrrole monomer or a chemical polymerization technique using 3,4-ethylenedioxythiophene (EDOT).

[0041] However, electrolytic polymerization technology and chemical polymerization technology have technical limitations and disadvantages, respectively.

[0042] Therefore, there is an increasing demand for the development of high-reliability tantalum capacitors that are excellent in heat resistance and moisture load resistance among high-reliability capacitors (particularly, capacitors for electric fields).

[0043] According to an embodiment of the present disclosure, the solid electrolyte layer 130 includes a first layer 130 a including an electrolytically polymerized conductive polymer disposed on the sintered body 110 and a second layer 130 b including a chemically polymerized conductive polymer disposed on the first layer 130 a .

[0044] The first layer 130 a includes an electrolytically polymerized conductive polymer and is formed by electrolytic polymerization. The first layer 130 a may be disposed on the sintered body 110 , and in particular, may be in contact with a dielectric oxide layer disposed on the sintered body 110 .

[0045] The second layer 130 b includes a chemically polymerized conductive polymer, is formed by chemical polymerization, and is disposed on the first layer 130 a .

[0046] In the case of forming the first layer 130a by electrolytic polymerization, a uniform and high-strength polymer film can be formed inside the semi-finished product, and a high capacitance voltage (CV) powder can be used during the process of applying power to form the polymer layer. Therefore, when the finished product is manufactured, it has the advantage of excellent moisture-proof properties.

[0047] However, in the case of electrolytic polymerization, there is a disadvantage that it is difficult to form a thick polymer film.

[0048] In addition, in the case of chemical polymerization, the cathode layer is formed by dipping the semi-finished product several times into a 3,4-ethylenedioxythiophene (EDOT) monomer solution, and a high-voltage resistant product can be obtained due to its excellent heat resistance. However, there are disadvantages in that the final product is susceptible to moisture and it is difficult to use high capacitance voltage (CV) powder due to uneven impregnation when the pores are clogged.

[0049] According to an embodiment of the present disclosure, a uniform cathode layer can be formed inside a tantalum capacitor by electrolytic polymerization of pyrrole and using high capacitance voltage (CV) powder, and the thickness of the cathode layer can be increased by an impregnation method using 3,4-ethylenedioxythiophene (EDOT) outside the tantalum capacitor.

[0050] Therefore, in this embodiment, it is possible to use high capacitance voltage (CV) powder, uniformly form a cathode layer and obtain a final product of a solid electrolytic capacitor having high capacity, high voltage, and excellent in heat resistance and moisture load resistance.

[0051] Specifically, according to an embodiment of the present disclosure, the first layer 130 a including an electrolytically polymerized conductive polymer is disposed on the sintered body 110 .

[0052] The first layer 130 a may be formed using high capacitance voltage (CV) powder, and may be formed by forming a polymer layer through electrolytic polymerization by applying power.

[0053] The first layer 130a may include polypyrrole.

[0054] In addition, the second layer 130b including the chemically polymerized conductive polymer is disposed on the first layer 130a.

[0055] The second layer 130 b may be formed through chemical polymerization by dipping the sintered body 110 several times into a 3,4-ethylenedioxythiophene (EDOT) monomer solution.

[0056] The second layer 130 b may include EDOT (3,4-ethylenedioxythiophene).

[0057] According to an embodiment of the present disclosure, since the first layer 130a is disposed on the sintered body 110 by electrolytic polymerization, when the second layer 130b is formed on the first layer 130a by chemical polymerization, the second layer 130b can be uniformly formed by dip coating because pores are not blocked.

[0058] Reference Figure 2 , a ratio t2 / t1 of a thickness t2 of the second layer 130b to a thickness t1 of the first layer 130a may satisfy 1.5≤t2 / t1≤10.0.

[0059] By adjusting the ratio t2 / t1 of the thickness t2 of the second layer 130b to the thickness t1 of the first layer 130a to satisfy 1.5≤t2 / t1≤10.0, a high capacitance-voltage (CV) powder can be used and the cathode layer can be uniformly formed, thereby realizing a high-capacitance, high-voltage solid electrolyte capacitor excellent in heat resistance and moisture resistance.

[0060] When the ratio t2 / t1 of the thickness t2 of the second layer 130b to the thickness t1 of the first layer 130a is less than 1.5, the thickness t2 of the second layer 130b is too thin, which results in poor moisture resistance and also has problems in heat resistance, making it difficult to realize high-voltage products.

[0061] When the ratio t2 / t1 of the thickness t2 of the second layer 130b to the thickness t1 of the first layer 130a exceeds 10.0, the thickness t2 of the second layer 130b is too thick, moisture resistance and heat resistance are improved, but there is a problem that it is difficult to realize a small high-capacity tantalum capacitor.

[0062] In addition, the solid electrolyte layer 130 may further include, for example, a layer formed using manganese dioxide (MnO2) on the second layer 130b. In order to form the manganese dioxide (MnO2) layer, the sintered body 110 on which the dielectric oxide layer is formed is impregnated with a manganese nitrate solution, thereby applying the manganese nitrate solution to the outer surface of the sintered body 110, and then sintering and a manganese dioxide (MnO2) layer having a cathode can be formed.

[0063] Next, the carbon layer 140 is stacked on the solid electrolyte layer 130, carbon powder is dissolved in an organic solvent containing an epoxy resin, the sintered body 110 on which the solid electrolyte layer 130 is formed is immersed in the solution in which the carbon powder is dissolved, and then dried at a predetermined temperature to volatilize the organic solvent. As an example, the carbon layer 140 may be formed on the second layer 130b.

[0064] In addition, the carbon layer 140 may serve to prevent silver (Ag) ions from passing therethrough.

[0065] Next, a silver (Ag) layer 150 formed using a silver (Ag) paste may be disposed on the carbon layer 140 .

[0066] A silver (Ag) layer 150 may be stacked on the outside of the carbon layer 140 to improve electrical conductivity.

[0067] In addition, the silver (Ag) layer 150 may improve the conductivity of the polarity of the cathode layer, thereby facilitating electrical connection for polarity transfer.

[0068] Figure 3 is a manufacturing process diagram of a solid electrolytic capacitor according to another embodiment of the present disclosure.

[0069] Reference Figure 3 , a method for manufacturing a solid electrolyte capacitor according to another embodiment of the present disclosure includes the following operations: operation S1, forming a sintered body by sintering; operation S2, forming a first layer including an electrolytically polymerized conductive polymer on the sintered body by electrolytic polymerization; and operation S3, forming a second layer including a chemically polymerized conductive polymer on the first layer by chemical polymerization.

[0070] In the method of manufacturing a solid electrolytic capacitor, first, a sintered body is formed by sintering.

[0071] In the method of forming the sintered body, the sintered body 110 is molded so that the anode lead 120 is disposed eccentrically from the sintered body 110. In more detail, for example, tantalum powder and a binder are mixed and stirred at a certain ratio, the mixed powder is pressed into a cuboid form, and then sintered at high temperature and high vibration to mold the sintered body 110.

[0072] In addition, the anode lead 120 is offset from the center of the sintered body 110 before the mixed powder is pressed, and the anode lead 120 is inserted into and mounted on the sintered body 110 so that one end of the anode lead 120 protrudes to the outside. Thereafter, an insulating layer and a solid electrolyte layer 130 as a cathode layer are formed on the sintered body 110.

[0073] According to another embodiment of the present disclosure, the operation of forming the solid electrolyte layer 130 includes forming a first layer including an electrolytically polymerized conductive polymer on a sintered body by electrolytic polymerization and forming a second layer including a chemically polymerized conductive polymer on the first layer by chemical polymerization.

[0074] Specifically, according to another embodiment of the present disclosure, the first layer 130 a including the electrolytically polymerized conductive polymer is formed on the sintered body 110 .

[0075] The first layer 130 a may be formed using high capacitance voltage (CV) powder, and may be formed through electrolytic polymerization by applying power.

[0076] The first layer 130a may include polypyrrole.

[0077] Next, the second layer 130b including the chemically polymerized conductive polymer is formed on the first layer 130a.

[0078] The second layer 130 b may be formed through chemical polymerization by dipping the sintered body 110 several times into an EDOT (3,4-ethylenedioxythiophene) monomer solution.

[0079] The second layer 130 b may include a polymer of 3,4-ethylenedioxythiophene (EDOT).

[0080] According to another embodiment of the present disclosure, since the first layer 130a is formed on the sintered body 110 by an electrolytic polymerization method, when the second layer 130b is formed on the first layer 130a by a chemical polymerization method, the second layer 130b can be uniformly formed during impregnation because pores are not blocked.

[0081] Therefore, a high capacitance-voltage (CV) powder can be used, and a cathode layer can be uniformly formed, so that a high-capacity, high-voltage solid electrolytic capacitor excellent in heat resistance and moisture load resistance can be realized.

[0082] A carbon layer 140 and a silver (Ag) layer 150 may be sequentially stacked on the sintered body 110 on which the solid electrolyte layer 130 as the cathode layer is formed, thereby improving conductivity of the polarity of the cathode layer.

[0083] The other features are the same as those described above in the solid electrolytic capacitor according to the embodiment of the present disclosure, and thus a detailed description thereof will be omitted.

[0084] As explained above, according to the present disclosure, the solid electrolyte layer of a solid electrolyte capacitor may include a first layer including an electrolytically polymerized conductive polymer and a second layer including a chemically polymerized conductive polymer disposed on the first layer, so that a high capacitance-voltage (CV) powder can be used, and a cathode layer can be uniformly formed, and a high-capacitance, high-voltage solid electrolyte capacitor having excellent heat resistance and moisture resistance can be realized.

[0085] However, various and advantageous advantages and effects of the present embodiment are not limited to the above description and will be more easily understood in the course of describing specific embodiments of the present disclosure.

[0086] While exemplary embodiments have been shown and described above, it will be apparent to those skilled in the art that modifications and variations can be made without departing from the spirit and scope of the present disclosure as defined by the appended claims.

Claims

1. A solid electrolyte capacitor, comprising: Sintered bodies, comprising sintered metals; as well as a solid electrolyte layer disposed on the sintered body, wherein the solid electrolyte layer comprises a first layer comprising an electrolytically polymerized conductive polymer disposed on the sintered body and a second layer comprising a chemically polymerized conductive polymer disposed on the first layer, and The ratio t2 / t1 of the thickness t2 of the second layer to the thickness t1 of the first layer satisfies 1.5≤t2 / t1≤10.

0.

2. The solid electrolytic capacitor according to claim 1, wherein: The first layer comprises polypyrrole.

3. The solid electrolyte capacitor according to claim 1 or 2, wherein: The second layer comprises a 3,4-ethylenedioxythiophene polymer.

4. The solid electrolytic capacitor according to claim 1, wherein The metal includes one or more selected from the group consisting of tantalum, aluminum, niobium, vanadium, titanium, and zirconium.

5. The solid electrolytic capacitor according to claim 1, wherein The first layer is in contact with a dielectric oxide layer disposed on the sintered body.

6. The solid electrolytic capacitor according to claim 1, further comprising: a carbon layer disposed on the solid electrolyte layer; as well as A silver layer is disposed on the carbon layer.

7. The solid electrolytic capacitor according to claim 1, wherein: The solid electrolyte layer also includes a layer including manganese dioxide.

8. A method for manufacturing a solid electrolyte capacitor, comprising the following operations: forming a sintered body by sintering; forming a first layer including an electrolytically polymerized conductive polymer on the sintered body by electrolytic polymerization; forming a second layer including a chemically polymerized conductive polymer on the first layer by chemical polymerization, in, A ratio t2 / t1 of a thickness t2 of the second layer to a thickness t1 of the first layer satisfies 1.5≤t2 / t1≤10.

0.

9. The method according to claim 8, wherein: The first layer comprises polypyrrole.

10. The method according to claim 8 or 9, wherein: The second layer comprises a 3,4-ethylenedioxythiophene polymer.

11. The method according to claim 8, further comprising: A third layer is formed, the third layer including manganese dioxide and disposed on the second layer.

12. The method according to claim 8, wherein: The sintered body is formed by sintering a molded body containing a metal powder, wherein the metal powder includes one or more selected from the group consisting of tantalum, aluminum, niobium, vanadium, titanium, and zirconium.

13. The method according to claim 8, wherein: The first layer is in contact with a dielectric oxide layer disposed on the sintered body.

14. The method according to claim 11, further comprising the following operations: forming a carbon layer on the third layer; and A silver layer is formed on the carbon layer.

15. The method according to claim 8, wherein: The forming of the second layer by chemical polymerization is performed by dipping the sintered body into a 3,4-ethylenedioxythiophene monomer solution several times.

Citation Information

Patent Citations

  • Solid electrolytic capacitor and method for manufacturing the same

    CN103680987A